PEMENUHAN HAK NARAPIDANA KELOMPOK RENTAN KHUSUS LANSIA SEBAGAI UPAYA MEMENUHI KESEHATAN DI LEMBAGA PEMASYARAKATAN - Tajuddin, Rachmad Irfan; Subroto, Mitro (Universitas Nusa Cendana, 2024)
Elderly prisoners are at high risk of health problems, and the availability of facilities and access to health services in prisons are important factors that need to be researched. Fulfilling the rights of elderly prisoners is not only a moral obligation, but also the basis for creating a more humane prison environment. This research uses qualitative methods with an observation approach and literature study. The results and discussion show the urgency of fulfilling the rights of elderly prisoners in the context of health, rehabilitation and psychological aspects. Increasing access to health, rehabilitation programs and psychosocial support are efforts in Indonesia to ensure the fulfillment of the rights of elderly prisoners. The impact of non-optimal fulfillment of rights includes decreased health, psychological impacts, non-compliance with human rights principles, and obstacles to rehabilitation. Keywords: Rights of Elderly ; Prisoners; Correctional Institutions